Effect of Soaking Lactobacillus Plantarum and Acetic Acid (CH3COOH 0.5 M) on Moisture Content, Ash, and Thermal Stability of Goat Feet Gelatin at Different Ages - Hasma Hasma; Ratmawati Malaka; Muhammad Irfan Said; Fahrullah Fahrullah; Sukarne Sukarne (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Slaughter of animals from year to year is increasing because the number of slaughtering animals will have an effect on the waste of goat leg bones. Goat legs in slaughtering animals have not been used optimally by the general public. The purpose of this study was to determine the effect of soaking L. plantarum and acetic acid on water content, ash content and thermal stability of gelatin obtained from goat leg bones at different ages of 1, 2 and 3 years. This research method uses a completely randomized design (CRD) with a 2x3 factorial pattern. Factor a soaking in a solution of Lactobacillus plantarum and acetic acid (CH3COOH 0.5 M), factor b goat age 1, 2 and 3 years. It was repeated 5 times, with data processing using SPSS version 21. The results showed that water and ash content had a very significant effect (P<0.01) on goat age and acid immersion (L. plantarum and acetic acid). For the thermal stability of goat leg bone gelatin using DSC, the highest value was obtained in goat leg bone gelatin aged 3 years with acetic acid immersion which was 176.37 mW, while the lowest value was obtained in 2 year old goat bone gelatin with L. plantarum immersion was 159.57 mW.